2018
DOI: 10.1111/nyas.13594
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of vocals and lyrics with left temporal musicogenic epilepsy

Abstract: Whether the cognitive processing of music and speech relies on shared or distinct neuronal mechanisms remains unclear. Music and language processing in the brain are right and left temporal functions, respectively. We studied patients with musicogenic epilepsy (ME) that was specifically triggered by popular songs to analyze brain hyperexcitability triggered by specific stimuli. The study included two men and one woman (all right-handed, aged 35-55 years). The patients had sound-triggered left temporal ME in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…Musicogenic epilepsy is a rare form of reflex epilepsy in which seizures are triggered by musical stimuli, ranging from simple tones to complex symphonic music . A literature review between 1884 and 2018 found 123 cases of MRS. Only two cases were related to anti‐GAD‐Ab but none of them had SPS .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Musicogenic epilepsy is a rare form of reflex epilepsy in which seizures are triggered by musical stimuli, ranging from simple tones to complex symphonic music . A literature review between 1884 and 2018 found 123 cases of MRS. Only two cases were related to anti‐GAD‐Ab but none of them had SPS .…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had musical training which was suggested to predispose to musicogenic epilepsy . The pathophysiology involved in MRS has not been well defined . Nevertheless, most reports emphasized the emotional component as the causal factor in stimulation of the epileptogenic zone, implying a complex evoked response involving multiple cortical areas and association cortex rather than a pure auditory evoked response …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Since the first description by Critchley, 1 it was noted that the semiology of MS is consistent with temporal lobe semiology. This includes abdominal aura, 7,19 aura of fear, 20,21 olfactory aura, 19,22 psychic aura of deja vu, 23 oral or manual automatisms, 7,24,25 and psychomotor behavior. 24 Autonomic changes in blood pressure, heart rate, and respiratory rate have been documented.…”
Section: Clinical Features Musicogenic Triggers and Semiological Featmentioning
confidence: 99%